Construção de um aviário utilizando cobertura produzida a partir de material reciclado - Neves, Felipe Augusto Candil de Carvalho [UNESP]; Sevegnani, Kelly Botigeli [UNESP]; Alves, Amanda Sellarin [UNESP]; Pagassini, Jonas Akenaton Venturineli [UNESP]; Barduco, Analice Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In current times, with the emphasis given to sustainability in agriculture, observing the maintenance and increase of production, the products obtained, the quality of life of people engaged in this productive chain and reducing impacts on the environment, Agroecology has stood out as an option for families and rural communities seeking to produce agricultural inputs in order to raise their income through productions with less cost and less impact on the environment. Farming techniques aimed at the inclusion of man in harmony with the environment explored, no use of agrochemicals and the participation of sociocultural aspects in the means of production are part of Agroecology. In the meantime, appears in UNESP Experimental Campus in Registro, the Group of Agroecology Cataia, which has been developing agricultural extension activities through projects and quilting bees work in small Agroecology and Organic production sites located in Vale do Ribeira region.The group also conducts theoretical studies and discussions related to the theme of Agroecology occurred during weekly meetings throughout the semester.

Nos tempos atuais, com o destaque dado para a sustentabilidade na Agricultura, observando-se a manutenção e elevação da produção, da qualidade dos produtos obtidos, da qualidade de vida das pessoas inseridas nesta cadeia produtiva e a redução dos impactos no meio ambiente a Agroecologia tem se destacado como opção para famílias e comunidades rurais que buscam produzir insumos agrícolas visando elevar sua renda através de produções com menor custo e menor impacto sobre o ambiente. Técnicas agrícolas que visam a inserção do homem em equilíbrio com o ambiente explorado, a não utilização de produtos agroquímicos e a participação de aspectos sócio-culturais nos meios de produção fazem parte da Agroecologia. Nesse interim, surge na Unesp - Campus Experimental de Registro, o Grupo de Agroecologia Cataia, que vem desenvolvendo atividades de extensão rural através de projetos e multirões de trabalho em pequenos sítios de produção Agroecológica e Orgânica situados na região do Vale do Ribeira.O grupo também realiza estudos teóricos e debates relacionados ao tema da Agroecologia ocorridos durante reuniões semanais ao longo do semestre.
Keywords: Group of agroecology; Henhouse; Food safety; Grupo de agroecologia; Galinheiro; Segurança alimentar